Towards a reference model for knowledge management processes for software-developing organizations: validation by experts (2015)
This paper aims to present the results of content and structure validation of a proposal of a reference model for knowledge management (KM) processes for software-developing organizations. Particularly, experts on KM affiliated with Latin America based institutions were surveyed. They completed an online survey asking about the descriptive elements of the model processes, the potential relevance and feasibility of implementing the model processes across Latin American organizations, as well as the influence that a set of factors might have on successfully implementing the model processes. The results obtained showed a high level of consensus among experts with respect to meeting the criteria established for validation. In addition, areas for improvement were detected in the description of the model processes which serve as a departure point for adjusting and developing a new version of the model.